Curriculum Alignment between Global Competency Standards and Local Educational Practices in Multilingual School Contexts - Dedi Gunawan Saputra; Dina Destari; Noura Rizqyannisa Hidayat (Global Education : International Journal of Educational Sciences and Languages, 2024)
This study investigates the alignment between global competency frameworks and local educational practices, particularly in multilingual classrooms. With globalization influencing education, acquiring skills like intercultural communication and global citizenship is vital. However, integrating these competencies into local curricula remains inconsistent, especially in multilingual settings, where linguistic and cultural diversity pose challenges. Using qualitative methods such as curriculum mapping, teacher interviews, and classroom observations, the study identifies areas of alignment and misalignment. While global competencies are integrated into subjects like social studies and global health education, technical subjects like mathematics and science show less alignment. The study also highlights gaps in the development of intercultural competence and global communication skills, which are often underrepresented. Challenges like language barriers, the monolingual habitus of many schools, and limited professional development for teachers in multilingual contexts hinder the full implementation of global competencies. The study recommends improving curriculum integration of global competencies across all subjects and enhancing teacher training to support multilingual classrooms. Future research should explore regional variations in multilingual settings and how technology can aid in developing global competencies. Addressing these challenges will better prepare students for both local and global challenges in an interconnected world.